Coupon redemption behaviour: a Malaysian cross‐segment investigation. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of this paper is to examine differing attitudinal characteristics (attitude and subjective norms) and perceptions of coupon characteristics (coupon value and coupon expiration date) towards coupon redemption based on psychological and demographic segments of consumers who may well differ in their purchase motivations and accompanying decision making.Design/methodology/approach – Following a detailed literature review, the characteristics are examined by means of a structured questionnaire administered via "mall intercept" to a convenience sample in major shopping areas in Malaysia.Findings – Following a variety of statistical tests, the findings support the use of coupon proneness, value consciousness, price consciousness and brand involvement as separate variables underpinning coupon usage propensity and indicated the value of coupons if used judiciously in relation to pre‐identified segments.Research limitations/implications – The limitations associated with convenience sampling apply here, that is the findings cannot be generalised.Practical implications – The basis for sound parameters for the use of coupons are of value to marketing management.Originality/value – The paper offers an unique insight into coupon propensity and usage from a little‐known economy. Its value lies in the degrees of support offered to findings from more advanced economies and a basis for differentiation in the Malaysian context.